2022
DOI: 10.7554/elife.71846
|View full text |Cite
|
Sign up to set email alerts
|

Mapping dopaminergic projections in the human brain with resting-state fMRI

Abstract: The striatum receives dense dopaminergic projections, making it a key region of the dopaminergic system. Its dysfunction has been implicated in various conditions including Parkinson’s disease (PD) and substance use disorder. However, the investigation of dopamine-specific functioning in humans is problematic as current MRI approaches are unable to differentiate between dopaminergic and other projections. Here, we demonstrate that ‘connectopic mapping’ – a novel approach for characterizing fine-grained, overla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…The nature of its impact on systems that are core to dysfunction in the context of psychiatric disorders explains limited disorder-specificity, while also underscoring the relevance of investigating functions over classifications. With regards to the underlying biology, we observed brain-behavioral interactions in the dominant functional gradient, where earlier work found interactions to behavior in higher-level gradients [21,22]. We consider that our results underline the complexity of the functional organization of the striatum, where different overlapping gradients are associated with different biological mechanisms.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The nature of its impact on systems that are core to dysfunction in the context of psychiatric disorders explains limited disorder-specificity, while also underscoring the relevance of investigating functions over classifications. With regards to the underlying biology, we observed brain-behavioral interactions in the dominant functional gradient, where earlier work found interactions to behavior in higher-level gradients [21,22]. We consider that our results underline the complexity of the functional organization of the striatum, where different overlapping gradients are associated with different biological mechanisms.…”
Section: Discussionsupporting
confidence: 62%
“…The high test-retest reliability of connectopic maps compared to conventional measures of function or functional connectivity further highlights their potential in obtaining the type of single-subject brain function that allows for strong translational work to the clinic [20]. We have also shown that topographic connectivity in the striatum is related to complex goal-directed behaviors at the individual level [21], and shows a strong correspondence with the spatial distribution of dopaminergic projections, demonstrating their potential for investigating striatal function [22]. Because connectopic maps characterize complex regions such as the striatum in a way that links to behavior, we hypothesize that individual differences in connectopic maps are predictive of psychiatric symptomatology across disorders.…”
Section: Introductionmentioning
confidence: 76%
“…The nature of its impact on systems that are core to dysfunction in the context of psychiatric disorders explains limited disorder-specificity, while also underscoring the relevance of investigating functions over classifications. With regards to the underlying biology, we observed brain-behavioral interactions in the dominant functional gradient, where earlier work found interactions to behavior in higher-level gradients (22, 39). This indicates the complexity of the functional organization of the striatum, but also the necessity of investigating spatially overlapping patterns of connectivity in order to fully understand striatal involvement.…”
Section: Discussionmentioning
confidence: 84%
“…The latter is important because in striatum we have shown that the dominant mode of connectivity change distinguishes between caudate nucleus, nucleus accumbens and putamen, while the second mode follows a rostral-caudal gradient across the three striatal substructures (21). We have also shown that topographic connectivity in the striatum is related to complex goal-directed behaviors at the individual level (21), and shows a strong correspondence with the spatial distribution of dopaminergic projections, demonstrating their potential for investigating striatal function (22). Because connectopic maps characterize complex regions such as the striatum in a way that links to behavior, we hypothesize that individual differences in connectopic maps are predictive of psychiatric symptomatology across disorders.…”
Section: Introductionmentioning
confidence: 91%
“…As an example, constant stepwise connectivity changes along the gradient would result in increases in first-order and decreases in higher-order parameters, whereas a more clustered or complex functional organization would lead to diminished first-order and increased higher-order parameters. We chose the third model order based on previous studies and as a trade-off between model parsimony and explained variance, since the increase in explained variance using higher model orders was minimal [ 7 , 34 , 35 ]. In order to include biologically plausible gradients in the statistical analysis of the PREVENT-AD cohort, only participants whose dominant gradient preserved the main direction of the average HCP gradient were included for further analysis.…”
Section: Methodsmentioning
confidence: 99%